NARATIVE REVIEW KONTEN PUBLIKASI IMPLEMENTASI KEBIJAKAN DESENTRALISASI DAN OTONOMI DAERAH DI WILAYAH PERBATASAN - Tupan Tupan; Retno Asihanti Setiorini (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
Border areas are very lagging behind in the field of development when compared to development in neighboring countries. There are several problems that need to be resolved in the border areas with neighboring countries. The welfare of the people living in border areas needs to be considered. The purpose of writing is to conduct a narrative review of the published content of the implementation of decentralization and autonomy policies in border areas. The research was conducted using a narrative review method with searches through the ISJD database, garudaristekbrin.go.id, doaj.org, google scholar, and academic.microsoft.com/homes. The data collected were 18 articles that were appropriate to be grouped into 3 major themes, namely: implementation of decentralization and regional autonomy; border area problems; border area development. The results show that according to historical records, regional autonomy has been implemented in Indonesia since the days of the kingdom, colonialism, and the development period of the Law on Regional Autonomy, namely Law Number 1 of 1945. Border areas face the problem of disparity or gaps in regional growth and regional autonomy. socio-economic status in border areas with the phenomenon of rampant illegal logging activities, illegal trade, illegal migration flows, and the many shifts in the boundaries between countries. The solution to the problem of development in border areas offered by the author is asymmetric decentralization.